EKSISTENSI BAHASA DALAM HUKUM NEGARA - Christina Purwanti (FISIP Universitas Bung Karno, 2021)
AbstractThe existence of language in law is very interesting to study. The use of language in the field of law both conceptually and in legal practice must be understood and understood more deeply. The language used through words, sentences, and texts always gives dynamic and flexible meanings to law, not limited to literal or grammatical meanings. In other words, the language used in the field of law changes in meaning according to the context, situation, and purpose of its users. The purpose of writing this journal is to describe the existence of language in law through qualitative methods with an interdisciplinary approach. Key Word: language, law, meaning, change of meaning